MENINGKATAN MINAT MEMBACA MELALUI GERAKAN LITERASI SEKOLAH DI SDN BERU KECAMATAN SARIREJO - Heti Nur Ani; Agustinus Salukh; Annita Mahmudah; Aranta Prista Dilasari; Evi Dwi Kartikasari; Andik Wijaya; Ma'rufatur Rodhiyah (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
The word literacy is now very familiar to the public. We define someone who is literate as someone who is literate or can read. Reading has a very strong cultural influence on the literacy development of students. Unfortunately, student achievement at SDN Beru is still low. Therefore, in community service in Beru village, we held a literacy movement program to increase interest in reading. The implementation method applied is to provide assistance by interacting directly with students through teaching and learning activities in the classroom. The goal is that students at SDN Beru can read. The result of this service is that students gain new knowledge from the literacy movement.